Stability Theorems for a Mathematical Model SI with Vital Dynamics Structured by Sex for the Infection Free Steady developed by the Ordinary Differential Equations and the Delay Differential Equations respectively - Pino Romero, Neisser (2017)
In the present work, a Basic Model SI with Vital Dynamics Structured by Gender developed by the Ordinary Differential Equations (Transmission of contagion is instantaneous), and also developed in the DelayDifferential Equations (Transmission of contagion occurs after a certain period of time), where the Local and Asymptotic Stability Theorem is proposed The Free of Infection point for both models, respectively.